Facile synthesis of core/shell ZnO/ZnS nanofibers by electrospinning and gas-phase sulfidation for biosensor applications1. Issue 37 (7th October 2015) - Baranowska-Korczyc, Anna; Sobczak, Kamil; Dłużewski, Piotr; Reszka, Anna; Kowalski, Bogdan J.; Kłopotowski, Łukasz; Elbaum, Danek; Fronc, Krzysztof
<x xml:space="preserve">Abstract</x> This study describes a new method of passivating ZnO nanofiber-based devices with a ZnS layer.